2018
DOI: 10.21873/anticanres.11929
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Microcystic Adnexal Carcinoma with DNA Sequencing Results and Response to Systemic Antineoplastic Chemotherapy

Abstract: Microcystic adnexal carcinoma (MAC) is a rare cutaneous malignancy. Due to its rarity, the molecular characteristics and treatment for metastatic MAC remain undefined. Here we present, as far as we are aware, the first case of metastatic MAC with DNA sequencing results indicating a mutation in TP53 and chromosomal losses in cyclin dependent kinase inhibitor 2A (CDKN2A) and cyclin dependent kinase inhibitor 2B (CDKN2B). In addition, this is the first case of metastatic MAC with a documented objective response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…The same study reported inactivating TP53 mutations and frame-preserving indel mutations located in the kinase domain of JAK1, copy number alterations with gain of JAK2, MAF, MAFB, JUN, or FGFR1, and loss of CDKN2A. These data were consistent with another study in which sequencing indicated a mutation of TP53 with loss of CDKN2A and CDKN2B in metastatic MAC [74]. Another study reported that, unlike basal cell carcinoma, Hedgehog signaling was not significantly altered in MAC [75].…”
Section: Microcystic Adnexal Carcinomasupporting
confidence: 79%
“…The same study reported inactivating TP53 mutations and frame-preserving indel mutations located in the kinase domain of JAK1, copy number alterations with gain of JAK2, MAF, MAFB, JUN, or FGFR1, and loss of CDKN2A. These data were consistent with another study in which sequencing indicated a mutation of TP53 with loss of CDKN2A and CDKN2B in metastatic MAC [74]. Another study reported that, unlike basal cell carcinoma, Hedgehog signaling was not significantly altered in MAC [75].…”
Section: Microcystic Adnexal Carcinomasupporting
confidence: 79%
“…Recently, two studies proposed special molecular markers for MAC by systematically analyzing genetic changes through high-throughput sequencing at the DNA level. Chen et al demonstrated that TP53 mutations and chromosomal deletion of CDKN2A and CDKN2B existed in a metastatic MAC of a 68-year-old man [ 9 ]. There has been no study on the protein expression of p16 (which is encoded by CDKN2A ) in MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies revealed DNA changes by next-generation sequencing. Chen et al revealed TP53 mutations and chromosomal loss in cyclin-dependent kinase inhibitor 2A ( CDKN2A ) and cyclin-dependent kinase inhibitor 2B ( CDKN2B ) in a metastatic MAC case [ 9 ]. Chan et al demonstrated that inactivated TP53 or activated JAK/STAT signaling pathways play important roles in MAC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case reported, treatment was delivered over 7 weeks, including 70 Gy of intensity-modulated RT over 35 fractions to the primary site and 4 cycles of concomitant weekly carboplatin (area under the curve 1.5) and paclitaxel (30 mg/m 2 ), as carboplatin/paclitaxel have activity and act as a radio-sensitizer in head and neck cancers [ 50 ]. A recent single-institution retrospective study based on 53 cases demonstrated that the risk of recurrence increased by 11% per 1 cm 2 increase in tumor size [ 51 ].…”
Section: Tumors With Apocrine and Eccrine Differentiationmentioning
confidence: 99%